The Pattern of Distribution of Biopsied Oral Lesions in Basrah Province- A 20 Year Retrospective Study - Al Qudsi, Ghaydaa Hashim; Aljazaeri, Sundus Abdul Wadood; Fadil, Adil G. (Scientific Journal of Medical Research, 2020)
Objectives: This study aimed to evaluate the prevalence of oral lesions in Basrah province and compare with other reviews. Methods: A retrospective study, data obtained from the oral biopsy reports seen in the histopathology laboratory of Al Sadder Teaching Hospital and private laboratories in Basrah from 1981-2000. Following variables were analyzed: type of oral lesion, age, sex and site of distribution. Oral lesions classified into five major categories: inflammatory lesions, cystic lesions, neoplastic lesions, white lesions and tumour-like lesions. The age of patients grouped as follows: 1-15, 16- 30, 31-45, 46-60, and above 61 years. Site of distribution lesions includes palate, the floor of mouth, lips, tongue, gingiva, buccal mucosa, maxilla and mandible. Results: Among the 743 oral biopsy reports, 475 (63.9%) found in males and 268 (36.1%) were in females. Neoplastic lesions were the commonest oral lesions 514 (69.2%) followed by tumour-like lesions 116 (15.6%), cystic lesions 54 (7.3%), inflammatory lesions 35 (4.7%) and then white lesions 24 (3.2%). The first site was tongue 140 (18.8%), followed by lips 118 (15.9%) and the floor of the mouth 115 (15.5%)meanly between 46-60 years 205 (27.6%). Conclusion: The majority of oral lesions were in males, and it is of a neoplastic and tumour-like type. This will highlight the importance of prevention, early detection and diagnosis of such lesions.